ARCHAEOLOGICAL HERITAGE AND NATIONAL HISTORY: THE HISTORY OF RESEARCH IN UZBEKISTAN - Rasulov Gayrat Pardayevich, PhD (Western European Studies, 2025)
This article examines the formation and evolution of archaeological science in Uzbekistan, focusing on the scientific study of historical and cultural heritage sites and their contributions to national historiography. It analyzes large-scale research conducted during the years of independence, international archaeological expeditions, and the objectives outlined in the “Concept for the Development of Archaeological Science in Uzbekistan.” Additionally, the article explores early state formation processes in Uzbekistan during the Bronze Age, using archaeological evidence, with a particular emphasis on Bronze Age monuments
Keywords: Uzbekistan archaeology; archaeological research; historical-cultural heritage